2019
DOI: 10.1016/j.jsps.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and anti-diabetic, anti-inflammatory and antioxidant activities of Loranthus acaciae Zucc. Grown in Saudi Arabia

Abstract: The Loranthus genus has been demonstrated to be used in the treatment of wide range of diseases e.g. diabetes, inflammations and cancers. Many species of Loranthus represent a major source of biologically active constituents. Therefore, our study was carried out to investigate the anti-diabetic, anti-inflammatory and antioxidant effects of Loranthus acaciae Zucc. (Loranthaceae) grown in Saudi Arabia. Moreover, our research concerned the guided-fractionation and isolation of possible active compounds from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…These results agree with previous phytochemical studies that indicate that flavonoids, such as catechin, quercetin, rutin, gallic acid, methyl gallate, and loranthin, a new flavanocoumarin, are the major active constituents of PA that contribute to its high radical scavenging activity [ 16 , 17 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results agree with previous phytochemical studies that indicate that flavonoids, such as catechin, quercetin, rutin, gallic acid, methyl gallate, and loranthin, a new flavanocoumarin, are the major active constituents of PA that contribute to its high radical scavenging activity [ 16 , 17 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many phenolic compounds were isolated from PA (also named Loranthus Acacia ) such as catechin, quercetin, rutin, gallic acid, methyl gallate, and loranthin (a new flavanocoumarin), showed high antioxidant activities [ 16 ]. The phytochemical analysis of PA led to the isolation and characterization of four compounds namely, quercetin 3-O-b-Dglucopyranoside, quercetin 3-O-b-(6-O-galloyl)-glucopyranoside, (−) catechin, and catechin 7-O-gallate [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical analysis of L acaciae led to the isolation and characterization of quercetin 3-O-ꞵ-D-glucopyranoside, quercetin 3-O-ꞵ-(6-O-galloyl)-glucopyranoside, (-) catechin, and catechin 7-O -gallate. Among these compounds quercetin 3-O-ꞵ-Dglucopyranoside, quercetin 3-O-ꞵ-(6-O-galloyl)glucopyranoside and catechin 7-O-gallate, were isolated for the first time from this species (Noman et al, 2019). In Plicosepalus curviflorus (Oliv.)…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a in vitro study about the anti-diabetic properties from hemiparasitic species of D. falcata revealed that its plant's leaves extracts had inhibitory activity on the key enzyme alpha-amylase, which enzyme breaks the large strach molecules that produces free glucose and simultaneously increases the blood sugar level, and consequently hyperglycemia (Naskar et al, 2019). Likewise, the cloroform fraction and crude extract from Loranthus acaciae Zucc grown in Saudi Arabia showed anti-diabetic, anti-inflammatory and antioxidant activities (Noman et al, 2019). Leaves from Scurrula parasitica L., quercetin, quercitrin, kaempferol 3-O-α-Lrhamnoside, (+)-catechin compounds, together with ethyl acetate and methanol extracts exhibited effective antioxi-dant activities against DPPH(2,2-diphenyl-1-picrylhydrazyl), ABTS[2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)] and FRAP (Ferric reducing antioxidant potential), while n-hexane and other compounds were inactive (Muhammad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, phytochemical investigations have led to the isolation and identification of phenolic compounds exhibiting free radical scavenging activity [11,12]. We recently reported about the antidiabetic, anti-inflammatory, and antioxidant activities, as well as isolation and identification of four flavonoid derivatives, namely, quercetin 3-O-β-d-glucopyranoside, quercetin 3-O-β-(6-O-galloyl)-glucopyranoside, (−)-catechin, and catechin 7-O-gallate, from the chloroform fraction of L. acaciae [13]. Furthermore, several other studies have demonstrated the anticancer properties of various members of the Loranthaceae family, such as Loranthus micranthus, Loranthus parasiticus, and Loranthus ferrugineus [14][15][16].…”
Section: Introductionmentioning
confidence: 99%